Variations in the radiographic appearance of a nasal adenocarcinoma over time - LAMB, C. R.; GREGORY, S. P.; BROCKMAN, D.; MANTIS (Π.Σ. ΜΑΝΤΗΣ) P. S.; DOBSON, J. (Journal of the Hellenic Veterinary Medical Society, 2018)
A 9 year old, neutered male, mixed breed dog had epistaxis from the right nostril, right epiphora and marked upper respiratory noise. Initial radiographs revealed lesions typical of primary nasal neoplasia, but the biopsy was non-diagnostic. Subsequent radiographs, obtained one and two months later when the dog did not show any clinical signs, revealed radiographic signs typical of destructive rhinitis. Clinical signs recurred three months later and radiographic signs were again typical of advanced primary nasal neoplasia. Nasal adenocarcinoma was confirmed histopathologically. The principal reason for this unusual sequence of the radiographic findings is considered to be the temporary disappearance of a nasal mass, possibly because it became dislodged and was swallowed.